Congenital esophageal stenosis with tracheoesophageal window - D´Alessandro Pablo D; Reusmann Aixa; Rubio Martin A; Cocciaglia Alejandro; Boglione Mariano M (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
There are different types of congenital anomalies who have its origin in the embryological development of the esophagus and trachea at the fifth and seventh weeks. Examples of these are Laryngotracheoesophageal clefts, esophageal atresia with or without fistula and Congenital Esophageal Stenosis (CES) [1-3]. The following case expose a 28-days-old baby boy with a extrange type of tracheoesophageal fistula with an esophageal estenosis.